Communication Strategies Used by English Lecturer in EFL Classroom Interaction Second Semester at STKIP Taman Siswa Bima - Nurhidayat Nurhidayat; Fitri Ningsi; Ika Irawati (STKIP Yapis Dompu, 2023)
This research was aimed to find out the kinds of communication strategies which are used by the lecturers and to find out how the lecturers used communication strategies in communicating with their students in teaching speaking subject at English Department of STKIP Taman Siswa Bima. This research applied descriptive qualitative method, more specifically classroom discourse analysis. The data were collected from the observation by audio recorder during one meeting from two lecturers at English Department of Muhammadiyah University of Makassar, in order to find out what are the kinds of communication strategies are used by the lecturers and the ways lecturers used communication strategies in communication with their students. The result of this research showed that there were three communication strategies which were appeared when the lecturers communicating with their students during the teaching activity, they were achievement or compensatory strategies, stalling or time gaining strategies and the last was interactional strategies. The lecturers use L1 so that students more easily understand what was conveyed by the lecturers when students experience difficulties in L2. This is due to the fact that students still have less knowledge of English and the lecturers adapted to the situation by following them using much L1 in order to make them easier to learn English.